The effect of exercise to improve quality of life among patients with heart failure: A literature review - Masroni Masroni; Ni Made Manik Elisa Putri; Anita Dwi Ariyani (Malahayati International Journal of Nursing and Health Science, 2020)
Background: Nowadays, cardiovascular diseases are considered as the most prevalent disease in developed countries and are main cause of mortality in all ages and races. Heart failure (HF) is a major public health issue in the world. An exercise program, developed based on the physical conditions of patients, can promote the quality of life in heart failure patients.Purpose: To examine the effect of exercise to improve quality of life among patient with Heart Failure.Methods: The electronic databases of PubMed, CINAHL, Trip, and Cochrane Systematic Reviews were searched. These databases were chosen based on their inclusion of allied health and medical journals, and those that contain studies relevant based exercise.Results:  The search terms included "heart failure", "exercise", "quality of life". We found 272 articles in all databased and got 1 for PubMed, 2 for Trip database that fit in criteria.Conclusion: Physical exercise has proved increasing quality of life among patients with heart failure. Improving patients exercise capacity and increasing their ability to perform more daily physical activity is expected to improve their quality of life. From the result finding of three evidences, we could see the significant finding on increasing quality of life after did physical exercise.